Comparison of Activation Patterns in Mirror Neurons and the Swallowing Network During Action Observation and Execution: A Task-Based fMRI Study - Jing, Ying-hua; Lin, Tuo; Li, Wan-qi; Wu, Cheng; Li, Xue; Ding, Qian; Wu, Man-feng; Xu, Guang-qing; Lan, Yue (Frontiers in Neuroscience, 2020)
Background: Observation of a goal-directed motor action can excite the respective mirror neurons, and this is the theoretical basis for action observation (AO) as a novel tool for functional recovery during stroke rehabilitation. To explore the therapeutic potential of AO for dysphagia, we conducted a task-based functional magnetic resonance imaging (fMRI) study to identify the brain areas activated during observation and execution of swallowing in healthy participants. Methods: Twenty-nine healthy volunteers viewed the following stimuli during fMRI scanning: an action-video of swallowing (condition 1, defined as AO), a neutral image with a Chinese word for "watching" (condition 2), and a neutral image with a Chinese word for "swallowing" (condition 3). Action execution (AE) was defined as condition 3 minus condition 2. One-sample t-tests were performed to define the brain regions activated during AO and AE. Results: Many brain regions were activated during AO, including the middle temporal gyrus, inferior frontal gyrus, pre-and postcentral gyrus, supplementary motor area, hippocampus, brainstem, and pons. AE resulted in activation of motor areas as well as other brain areas, including the inferior parietal lobule, vermis, middle frontal gyrus, and middle temporal gyrus. Two brain areas, BA6 and BA21, were activated with both AO and AE. Conclusions: The left supplementary motor area (BA6) and left middle temporal gyrus (BA21), which contains mirror neurons, were activated in both AO and AE of swallowing. In this study, AO activated mirror neurons and the swallowing network in healthy participants, supporting its potential value in the treatment of dysphagia.